The genetic architecture of shoot–root covariation during seedling emergence of a desert tree, Populus euphratica. (9th April 2017) - Zhang, Miaomiao; Bo, Wenhao; Xu, Fang; Li, Huan; Ye, Meixia; Jiang, Libo; Shi, Chaozhong; Fu, Yaru; Zhao, Guomiao; Huang, Yuejiao; Gosik, Kirk; Liang, Dan; et al.
Summary: The coordination of shoots and roots is critical for plants to adapt to changing environments by fine‐tuning energy production in leaves and the availability of water and nutrients from roots. To understand the genetic architecture of how these two organs covary during developmental ontogeny, we conducted a mapping experiment using Euphrates poplar ( Populus euphratica ), a so‐called hero tree able to grow in the desert. We geminated intraspecific F1 seeds of Euphrates Poplar individually in a tube to obtain a total of 370 seedlings, whose shoot and taproot lengths were measured repeatedly during the early stage of growth. By fitting a growth equation, we estimated asymptotic growth, relative growth rate, the timing of inflection point and duration of linear growth for both shoot and taproot growth. Treating these heterochronic parameters as phenotypes, a univariate mapping model detected 19 heterochronic quantitative trait loci ( h QTLs), of which 15 mediate the forms of shoot growth and four mediate taproot growth. A bivariate mapping model identified 11 pleiotropic h QTLs that determine the covariation of shoot and taproot growth. Most QTLs detected reside within the region of candidate genes with various functions, thus confirming their roles in the biochemical processes underlying plant growth. Significance Statement: To adapt to changing environments, it is necessary for plants to coordinate energy production in leaves with the availability of water and nutrients from roots. Here we measured seedling growth parameters in a mapping population of Euphrates Poplar and thereby identified heterochronic quantitative trait loci ( h QTLs) that might underlie covariation between shoot and taproot growth.